How essential is the essential resilience scale? Differential item functioning of Chinese and English versions and criterion validity. (1st March 2020) - Lau, Chloe; Chiesi, Francesca; Saklofske, Donald H.; Yan, Gonggu; Li, Catherine
Abstract: The Essential Resilience Scale (ERS) is a locally developed measure conceptualized by Chinese researchers and demonstrated strong psychometric properties in Chinese residents. The present study recruited undergraduate students from China ( N  = 375) and Canada ( N  = 378) to complete the ERS and criterion validity measures (i.e., Resiliency Scale for Young Adults, Satisfaction with Life Scale). Both the Chinese and English versions of the ERS were associated with Resiliency Scale for Young Adults subscales and satisfaction with life in the expected directions. The item response theory parameterization using Samejima's graded response model showed discrimination parameters ranged from 1.02 to 2.22 and 0.32 to 1.97 in the Chinese and English versions, respectively. Differential item functioning (DIF) analyses showed six of 15 items were flagged for DIF; five of these items showing nonuniform DIF revealed more discriminant items for the Chinese version compared to the English version. Cross-cultural comparisons between these measures could present biases if not corrected for DIF. Implications on cross-cultural conceptualization of resiliency are discussed.